Thermodynamic optimization of parallel and spiral plate heat exchangers for modified solar thermal brayton cycle models (2022)
The receiver and heat exchangers in a Solar Thermal Brayton Cycle (STBC) have been the main sources of exergy loss. Duct profiles used in the heat exchange process have been observed to possess varying degrees of heat transfer effectiveness. To this end, the effects of the elliptical, circular and rectangular absorber tubes are investigated on three variants of the dual serial-regenerative STBC models employing reheater, intercooler, or in a combined arrangement. Also, the impact of the parallel plate heat exchanger (PPHE) and spiral plate heat exchangers (SPHE) on irreversibility is investigated. The particle swarm algorithm (PSA), a stochastic optimization tool is used for the minimization of irreversibilities within the cycle and optimization of the geometric parameters of the STBC components. The largest irreversibility loss on a component-basis is observed on the receiver. The rectangular absorber system for the receiver has the least irreversibility loss compared to other profiles studied, though, a higher internal to external irreversibility ratio was noticed. Improved exergy use via the dual regenerative system was observed on all models with reductions of 22% and 15% in irreversibility obtained from the receiver and recuperator respectively. In addition, the SPHE produced less irreversibilities compared to the PPHE system and this could be attributed to its large surface area available for heat transfer. An optimal second law efficiency of 62% and 74% on the PPHE and SPHE STBC systems, respectively is achieved at around a pressure ratio of 2.2. The dual serial-regenerative sys- tem without reheats and intercooling has the advantage of optimal energy available and efficient exergy use followed by the combined system.